2020
DOI: 10.21203/rs.3.rs-120941/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Labor Dystocia and Risk of Histological Chorioamnionitis and Funisitis: A Study from a Single Tertiary Referral Center

Abstract: Background: Intrauterine inflammation affects short- and long-term neonatal outcomes. Histological chorioamnionitis and funisitis are acute inflammatory responses in the fetal membranes and umbilical cord, respectively. Although labor dystocia includes a potential risk of intrauterine inflammation, the risk of labor dystocia in histological chorioamnionitis and funisitis has not been evaluated yet. This study aimed to examine the association between labor dystocia and risk of histological chorioamnionitis and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…We noted that although previous studies have identified nullipara, fetal macrosomia, older maternal age, infertility treatment as risk factors for dystocia [4,5,26,27], data on the association between pre-pregnancy BMI and dystocia or optimal gestational weight gain to reduce the risk of dystocia have not been comprehensively examined among nulliparous women.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We noted that although previous studies have identified nullipara, fetal macrosomia, older maternal age, infertility treatment as risk factors for dystocia [4,5,26,27], data on the association between pre-pregnancy BMI and dystocia or optimal gestational weight gain to reduce the risk of dystocia have not been comprehensively examined among nulliparous women.…”
Section: Discussionmentioning
confidence: 91%
“…The main strength of our study is that the data were derived from two tertiary care Maternal-Fetal medical units where all women who delivered were managed using approximately the same protocol [5,37]. Furthermore, all participants in this study were Japanese women and, therefore, there were no effects of ethnic diversity on measured outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition of GDM used in our institution has already been reported elesewhere 14 LD was defined as follows: a case with the cephalic presentation without a history of cesarean section (CS) and either operative vaginal delivery with several trials of maternal effort, due to arrest of the active phase for at least 4 h when the dilation of the cervix was 10 cm with or without an augmentation agent, or no progress in cervical dilation despite clinically adequate effective labor, irrespective of augmentation, such as the use of oxytocin or amniotomy. 15 Methods of delivery were categorized as emergent cesarean section or other. In clinical settings, emergent CS is usually conducted based on the attending doctor's decision, such as in cases of nonreassuring fetal status and LD.…”
Section: Discussionmentioning
confidence: 99%